Alterações fenotipicas e transcricionais em linfócitos T de uma população idosa em risco imune no sul do Brasil - Ornaghi, Ana Paula Maciel (2013)
The elderly population, characterized as people over 60 years old, has grown rapidly in recent years in Brazil, and with this increase in life expectancy, age-related changes appear, for example, immunosenescence. Some studies have shown that there are differences in the immunological profile of the elderly, often related to the numbers of T cells. The immune risk profile (IRP) has been defined as CD4/CD8 T-cell ratio <1 and positivity for serum anti-cytomegalovirus (CMV) antibodies. In this study, we investigated patterns of activation and differentiation of T lymphocytes by flow cytometry in an elderly population in IRP, compared with elderly people without risk profile (non-IRP), seeking to identify additional markers for this risk profile immune. For this study we recruited 60 elderly SUS patients in Porto Alegre, aged 60 years, 30 IRP and 30 non-IRP. Lymphocytes were isolated and stimulated in vitro to evaluate the production of cytokines and the expression of transcription factors. The subpopulations of T lymphocytes found were consistent with previous studies in which IRP patients had fewer naive and central memory T cells, as well as an increase was observed in the percentage of T cells CD8 + CD28-T cells and CD8 + PD-1 + in the IRP individuals. Furthermore, there was a reduction in mean fluorescence intensity (MFI) of transcription factors to canonical subtypes of T cell help (CD4 +) in IRP patients when compared to patients without IRP. The percentages of the different subtypes (TH1, TH2, TH17; Treg) of these cells were not different between the two groups. After stimulation with anti-CD3/anti-CD28 antibodies in culture for 24 hours, the concentration of cytokines in culture supernatants increased, but no significant differences between the two groups were found, except for IL-10, which was higher in IRP patients before stimulation. These results suggested that transcriptional mechanisms important in the differentiation of helper T cells are altered in IRP patients, which may affect the immune response of these individuals.